Who Is Takatāpui? Māori Language, Sexuality and Identity in Aotearoa/New Zealand - Murray, David A.B. (Anthropologica, 2022)
This paper is an introductory investigation into the complex relations between sexuality, language and Maori indigenous identity in Aotearoa/New Zealand. Through an examination of the development and proliferation of a Maori language term (takatdpui) for "gay" and "lesbian" Maori over the past 20 years, I analyze the socio-political implications of language use in identity discourses and the multiple interpretative possibilities that may be generated when a subaltern or minority language is utilized in relation to a minority identification located in an Anglo-postcolonial society